(untitled) (Scientific journal of the Fergana State University, 2024)
The article presents information on the prevalence and species composition of representatives of the Tortricidae family in the orchards of Central Fergana. Among the identified species, Cydia pomonella and Grapholita molesta are widespread in the orchards. Lobesia botrana and Argyrotaenia ljungiana were identified for the first time in the study area. Also, Selenodes karelica and Grapholita compositella, which were identified during our research, were noted for the entomofauna of Uzbekistan for the first time. An analysis of the studies conducted on the Tordricidae family in Uzbekistan is also presented. According to the results of the research, 2 subfamilies, 8 tribes and 51 species belonging to 25 genera were observed in the territory of Uzbekistan, of which 28 species were not found during further research.